Tracheal Stenosis due to Trachesotomy - Attaufany, Fahmi; Dewi, Yussy Afriani; Samiadi, Dindi; Permana, Agung Dinasti; Aroeman, Nurakbar (Majalah Anestesia dan Critical Care, 2015)
Tracheal stenosis is a condition where there is a narrowing of the diameter of the trachea. This condition can occurin congenital or acquired. Approximately 90% due to trauma: internal (prolonged intubation, tracheostomy, etc)with remaining due to external trauma (blunt trauma or penetrating trauma).The incidence of tracheal stenosisapproximately 4%–13% in adults and 1%–8% in neonates. The incidence of tracheal stenosis in Dept ORL-HNSDr. Hasan Sadikin General Hospital Bandung from January 2012–August 2013 as much as ive cases. We presenteda a man, 27 years old, suffer with complain of dyspnea. We found tracheal stenosis grade II (Myer-Cotton) afterlexible bronchoscopic examination due to previous tracheostomy.Tracheostomy was perform followed byinstallation tracheal tube and observation. Two years later the tracheal tube removed and continued with stomalclosure.